Suicide and Other-Cause Mortality after Early Exposure to Smoking and Second Hand Smoking: A 12-Year Population-Based Follow-Up Study. - Vincent Chin-Hung Chen (PLoS ONE, 2015)
Background The association between smoking and suicide is still controversial, particular for early life cigarette smoking exposure. Few studies have investigated this association in adolescents using population-based cohorts, and the relationship with second hand smoking (SHS) exposure has not been addressed. Methods and findings In this study, we followed a large population-based sample of younger people to investigate the association between smoking, SHS exposure and suicide mortality. Between October 1995 and June 1996, 162,682 junior high school students ages 11 to 16 years old living in a geographic catchment area in Taiwan were enrolled and then followed till December 2007 (1,948,432 person-years) through linkage to the National Death Certification System. Participants who were currently smoking at baseline had a greater than six-fold higher suicide mortality than those who did not smoke (29.5 vs. 4.8 per 100,000 person-years, p<0.001) as well as higher natural mortality (33.7 vs. 10.3 per 100,000 person-years, p<0.001). After controlling for gender, age, parental education, asthma, allergic rhinitis, and alcohol consumption, the adjusted hazard ratios for suicide were 3.69 (95% CI 1.85-7.39) in current smokers, and 1.47 (95% CI 0.94-2.30) and 2.83 (95% CI 1.54-5.20) respectively in adolescents exposed to SHS of 1-20 cigarettes and >20 cigarettes/per day. The estimated depression-adjusted odds ratio did not change substantially. The population attributable fractions for suicide associated with smoking and heavy SHS exposure (>20 cigarettes/per day) were 9.6% and 10.6%, respectively. Conclusions This study showed evidence of excess suicide mortality among young adults exposed to active or passive early life cigarette smoking.